KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH TERHADAP PENINGKATAN SARANA PRASARANA - Irjus Indrawan; Desvi Dahlia; Surahmat Surahmat; Buana Mustikawati; Wulandari Wulandari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze school operational assistance policies towards improving facilities and infrastructure. This research uses a descriptive qualitative research type by descriptively explaining qualitative data taken from various articles. The method used is systematic literature review (SLR). The results of this research show that the procurement of school facilities and infrastructure still requires clear and sufficient funding sources. Where before procuring all the facilities and infrastructure that will be used, you must make a clear plan for the needs and expenditure of money that will be used. Facilities and infrastructure that have been met can be put to good use to support the smooth running of learning and attention must be paid to their maintenance.